2014
DOI: 10.1002/stem.1666
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Regulates Neurogenesis and Protects Neural Progenitor Cells Against Aβ Toxicity

Abstract: Neural stem/progenitor cells (NPCs) proliferate and produce new neurons in neurogenic areas throughout the lifetime. While these cells represent potential therapeutic treatment of neurodegenerative diseases, regulation of neurogenesis is not completely understood. We show that deficiency of nuclear factor erythroid 2-related factor (Nrf2), a transcription factor induced in response to oxidative stress, prevents the ischemia-induced increase in newborn neurons in the subgranular zone of the dentate gyrus. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 71 publications
6
96
0
Order By: Relevance
“…68 Furthermore, Nrf2 is essential for neuronal differentiation of neural stem/progenitor cells, regulates injuryinduced neurogenesis, and provides protection against amyloid-beta-induced toxicity. 69 Being in the potential promoter of ENC1, the methylation of rs16872141 could potentially suppress transcription of this gene. However, rs16872141 was not significant in GWAS studies of the Swedish samples used in the present study (P-value = .303; 5001 cases and 6243 controls), 28 nor the recent PGC2 metaanalysis (P-value = .739; 36 989 cases and 113 075 controls).…”
Section: Discussionmentioning
confidence: 99%
“…68 Furthermore, Nrf2 is essential for neuronal differentiation of neural stem/progenitor cells, regulates injuryinduced neurogenesis, and provides protection against amyloid-beta-induced toxicity. 69 Being in the potential promoter of ENC1, the methylation of rs16872141 could potentially suppress transcription of this gene. However, rs16872141 was not significant in GWAS studies of the Swedish samples used in the present study (P-value = .303; 5001 cases and 6243 controls), 28 nor the recent PGC2 metaanalysis (P-value = .739; 36 989 cases and 113 075 controls).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nrf2-deficiency prevents ischemia-induced neurogenesis, suggesting the involvement of this transcription factor in regenerative processes after acute brain pathology [116] . Very recently Nrf2 gene transfer was shown to be protective in acute nerve damage [117] .…”
Section: Sci Induces Death Of Neuronal and Glial Cells As Well As Inmentioning
confidence: 99%
“…While several studies have investigated the role of the Keap1-Nrf2 system in stem cells knockdown studies that under physiological conditions Nrf2 functions in the promotion of proliferation and neuronal differentiation of NSCs without influencing their migration [204] .…”
Section: Endogenous Neurogenesis and Functions Of Nrf2 In Neural Stemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it was shown that NRF2 is essential for ischemia-induced neurogenesis in the SGZ niche [123]. In vitro, ectopic expression of NRF2 or treatment with a NRF2 activating compound, pyrrolidine dithiocarbamate, increases NSPCs self-renewal under proliferating conditions and supports neuronal differentiation upon mitogen withdrawal [123].…”
Section: Nrf2 Signalingmentioning
confidence: 99%